Energy-reduced diets supplemented with xylanase, Bacillus sp., and yeast wall maintain bone parameters, gut morphometry, economic indices, and performance of pigs - Justino, Lucas Rodrigo; Souza, Christiane Silva; Vasconcelos, Bruno da Silva de; Costa, Jessica Amaral; Quaresma, Débora Vaccari; Dilelis, Felipe; Vieira, Antonio Assis; Lima, Cristina Amorim Ribeiro de (Brazilian Journal of Animal Science, 2024)
This study aimed to investigate the effects of xylanase (Xyl) individually or in combination with B. subtilis and B. licheniformis associated or not with yeast cell wall in pig diets with a reduction of 100 kcal/kg of metabolizable energy (ME) content. Pig performance, bone parameters, intestinal morphometry, and bioeconomic indices were evaluated. A total of 75 pigs (25 females and 50 barrows; 25.02±3.21 kg) obtained from crossing Large White × Landrace were used. The experimental design consisted of randomized blocks, with five treatments and five blocks, totaling 25 experimental units subjected to treatments: basal diet (B); basal diet with reduction of 100 kcal/kg of ME (BEM); BEM with supplementation of xylanase (0.01%; BX); BX with supplementation of direct-fed microbials (composed of B. subtilis and B. licheniformis; 0.02%; BXM); and BX supplemented with 0.10% of symbiotic (which includes B. subtilis, B. licheniformis, and yeast cell wall; BXS). There were no differences in bone parameters. The BEM diet resulted in a lower villus height:crypt depth ratio in the jejunum than that seen upon using the BXS diet as feed. In the first period, pigs fed BEM diet had a 12% higher average daily feed intake than those fed the BXM diet. There were no differences in the pig performance during the second period. Over the total period, pigs fed BEM diet had greater FCR compared with pigs fed BXM diet. The inclusion of feed additives in diets with reduced ME content contributes to the maintenance of performance and characteristics of the metacarpus and jejunum of growing pigs and provides better bioeconomic indices.
Keywords: Bacillus; Energy restriction; Feed additive; Nutrition; Swine